Double-Crop Sunflower Cost-Return Budget in Central and Kansas - Lubben, Bradley D.; Staggenborg, Scott A. (My University, 2003)
This publication provides estimated cost and returns for forward farm planning for a double-crop sunflower production system in central and eastern Kansas.
MF2145_2003_10
Keywords: MF2145; Crops; Economics; MF